Predictors of long-term symptom burden and quality of life in patients hospitalised with chest pain: a prospective observational study - Tone Merete Norekvål; Jørund Langørgen; Torbjørn Omland; Øyvind Skadberg; Kjell Vikenes; Nasir Saeed; Ole-Thomas Steiro; Hilde Lunde Tjora; Rune Oskar Bjørneklett; Vernon Vijay Singha Bonarjee; Øistein Rønneberg Mjelva; Kristin Moberg Aakre (BMJ Open)
Objective To describe the magnitude and predictors of symptom burden (SB) and quality of life (QoL) 3 months after hospital admission for acute chest pain.Design Prospective observational study.Setting Single centre, outpatient follow-up.Participants 1506 patients.Outcomes Scores reported for general health (RAND-12), angina-related health (Seattle Angina Questionnaire 7 (SAQ-7)) and dyspnoea (Rose Dyspnea Scale) 3 months after hospital admission for chest pain.Methods A total of 1506 patients received questionnaires assessing general health (RAND-12), angina-related health (SAQ-7) and dyspnoea (Rose Dyspnea Scale) 3 months after discharge. Univariable and multivariable regression models identified predictors of SB and QoL scores. A mediator analysis identified factors mediating the effect of an unstable angina pectoris (UAP) diagnosis.Results 774 (52%) responded. Discharge diagnoses were non-ST elevation myocardial infarction (NSTEMI) (14.2%), UAP (17.1%), non-coronary cardiac disease (6.6%), non-cardiac disease (6.3%) and non-cardiac chest pain (NCCP) (55.6%). NSTEMI had the most favourable, and UAP patients the least favourable SAQ-7 scores (median SAQ7-summary; 88 vs 75, p<0.001). NCCP patients reported persisting chest pain in 50% and dyspnoea in 33% of cases. After adjusting for confounders, revascularisation predicted better QoL scores, while UAP, current smoking and hypertension predicted worse outcome. NSTEMI and UAP patients who were revascularised reported higher scores (p<0.05) in SAQ-7-QL, SAQ7-PL, SAQ7-summary (NSTEMI) and all SAQ-7 domains (UAP). Revascularisation altered the unstandardised beta value (>±10%) of an UAP diagnosis for all SAQ-7 and RAND-12 outcomes.Conclusions Patients with NSTEMI reported the most favourable outcome 3 months after hospitalisation for chest pain. Patients with other diseases, in particular UAP patients, reported lower scores. Revascularised NSTEMI and UAP patients reported higher QoL scores compared with patients receiving conservative treatment. Revascularisation mediated all outcomes in UAP patients.Trial registration number NCT02620202.